2007
DOI: 10.2753/jec1086-4415110402
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolving E-tail and On-Line Communities: Conceptual Framework

Abstract: This paper explores the problem of designing a Web site that meets the needs of both an evolving community and an evolving business. It reports a case study of a business that introduced an e-tail site and an associated on-line community. The site development used an existing community-centered development method. The study found that participants had different motivations for visiting the site-some only wanted product information and purchase, some were seeking social support and information, others sought a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…The existing body of knowledge also includes numerous publications related to website design (15 %) (e.g., Arazy et al 2010;Ganley 2011;Gottschlich et al 2013;Li and Buchthal 2012;Macaulay et al 2007;Mackenzie et al 2009;Noh et al 2013;Shi et al 2013;Wang et al 2007;Yue and Jiang 2013;Zhang and Liu 2013;Zhu et al 2010). Social shopping websites (82 %), presentation sites (12 %), and virtual worlds (6 %) were the social media platform types primarily investigated.…”
Section: Research Theme: Website Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing body of knowledge also includes numerous publications related to website design (15 %) (e.g., Arazy et al 2010;Ganley 2011;Gottschlich et al 2013;Li and Buchthal 2012;Macaulay et al 2007;Mackenzie et al 2009;Noh et al 2013;Shi et al 2013;Wang et al 2007;Yue and Jiang 2013;Zhang and Liu 2013;Zhu et al 2010). Social shopping websites (82 %), presentation sites (12 %), and virtual worlds (6 %) were the social media platform types primarily investigated.…”
Section: Research Theme: Website Designmentioning
confidence: 99%
“…Further publications investigate the effect of interactive social shopping features on website usage or purchase behavior (e.g., Jahng et al 2007;Macaulay et al 2007;Noh et al 2013;Olbrich and Holsing 2011;Wakefield et al 2010;Zhang and Liu 2013). For instance, Olbrich and Holsing (2011) found that the use of tags positively influences click-out behavior to the actual shop to purchase the product, while the use of lists and styles is negatively correlated with click-out behavior.…”
Section: Research Theme: Website Designmentioning
confidence: 99%
“…Such theories give explicit prescriptions on how to design and develop an artifact, whether it is a technological product or a managerial intervention [8]. An example of theory in this domain has been provided by Preece who advocates an iterative community-centered development approach to web site design because communities and their needs evolve over time, and web site design must in turn evolve [16] [25]. This model has been extended by Gregor and Jones [7] who have proposed a new "anatomical skeleton" for IS design theories, based on eight components which encompasses four issues identified in the Walls et al…”
Section: The Design Theory Frameworkmentioning
confidence: 99%
“…Moreover, IT systems features available to online community members must be appropriate to the task at hand and must satisfy their needs in terms of ease of use [16]. Therefore the community supporting platform is a critical success factor for community building as well as economic and social aspects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation